เบรคชท์กับฝรั่งเศส - นาควัชระ, เจตนา (Journal of the Faculty of Arts, Silpakorn University, 2021)
Brecht and France : The objective of the study is to assess Brecht's relations to France, their impact on his creativity and the image.of France as reflected in his works. On the basis of the examination of Brecht's own writings (including minor and lesser-known works), his private library, published as well as unpublished biographical, autobiographical and contemporary records and existing studies dealing with specific aspects of his contact with France, a fairly unified and consistent picture of this relationship has emerged, which more than confirms the hypothesis of the present research that France played an important role in Brecht's life and work. Although first-hand exposure to French life was limited to short occasional visits, France proved to be an intellectual treasure-house from which Brecht could derive benefits in terms of source-materials, socio-political ideas, dramaturgical principles and, above all, artistic inspirations. His knowledge of French literature, for example, is not to be underestimated. His attitude towards France and particularly French patriotism changed in the course of time, being skeptical at first, then sympathetic, and finally avowedly favourable. To him France was a battleground where the common people had the courage to fight a transnational Fascist conspiracy, a distinct socio-political pattern whose parallels he also discovered from his reading of French history. This "Matière de France", peopled with such characters as Joan of Arc, the Paris “Communards”, the “Résistance" fighters, fired his imagination to such an extent that he could create works of spiritual poignancy and artistic quality whose universal message transcended their topical relevancy. Through mature posthumous works like Die Gesichte der Simone Machard and Die Tage der Commune, Brecht was offering profound and complex images of the rise and fall of the people's liberation efforts without ever hesitating to name the enemy of the people, thereby pricking the conscience of many of the powers that be in both East and West. Intellectually and spiritually, Brecht was quite close to France. The claim made by his friend Vladimir Pozner about Brecht's love for France" is no exaggeration.